THE INVASIVE DENTAL PROCEDURES IN PATIENTS TREATING WITH WARFARIN: POSSIBILITIES AND PROSPECTS FOR SAFETY - T. V. Kozlova; I. M. Makeyeva; V. Y. Doroshina; S. I. Bokareva (Столичная издательская компания, 2016)
Details of the management of patients receiving oral anticoagulants (vitamin K antagonists) for a long time and needed in dental treatment are discussed. Assessment of bleeding and thromboembolism risk in the perioperative continuation or termination of warfarin therapy is shown. Potential of the local hemostatic agents is specified. Modifications of the patient dental health card are offered to prevent complications associated with blood clotting disorders.